2020
DOI: 10.1177/1550059419899324
|View full text |Cite
|
Sign up to set email alerts
|

P50, N100, and P200 Sensory Gating in Panic Disorder

Abstract: Panic disorder (PD) has been linked to abnormalities in information processing. However, only little evidence has been published for sensory gating in PD. Sensory gating describes the brain’s ability to exclude stimuli of low relevance from higher level information processing, thereby sustaining efficient cognitive processing. Deficits in sensory gating have been associated with various psychiatric conditions, most prominently schizophrenia. In this case-control event-related potential study, we tested 32 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…One possible reason is the relevance of attention since many scholars have suggested that the distraction paradigm may enhance the detection of abnormal gating in patients with schizophrenia (34). Consequently, visual and auditory distractors were given in the N100/P200 trials (20,33,35,36). However, Rosburg et al suggest that the active control of attention is difficult in sensory gating experiments, since long intervals of no stimulation between the paired clicks are a necessary component of these experiments (58).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One possible reason is the relevance of attention since many scholars have suggested that the distraction paradigm may enhance the detection of abnormal gating in patients with schizophrenia (34). Consequently, visual and auditory distractors were given in the N100/P200 trials (20,33,35,36). However, Rosburg et al suggest that the active control of attention is difficult in sensory gating experiments, since long intervals of no stimulation between the paired clicks are a necessary component of these experiments (58).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is the relevance of attention since many scholars have suggested that the distraction paradigm may enhance the detection of abnormal gating in patients with schizophrenia ( 34 ). Consequently, visual and auditory distractors were given in the N100/P200 trials ( 20 , 33 , 35 , 36 ). However, Rosburg et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations